Evolução, religião e ambiente (Evolution, religion and environment) - DOI: 10.5752/P.2175-5841.2010v8n17p109 - Christoffersen, Martin Lindsey (Horizonte, 2010)
In this International Year for the Conservation of Biodiversity, I reflect on the increasing responsibilities of religious entities towards solving the present Environmental Crisis. I provide a retrospect on the debate over the origin of religions in the context of the cultural evolution of man. I then mention some ecological dimensions of religious thinking, which are particularly significant for approaching environmental problems. Religious paradigms originate in ways that are similar to those in science. The social doctrines of churches establish compromises for excluded groups and promote the unabridged development of the human individual, which includes social and economic justice. This has implications for the ecological balance of nature and for the future of humanity. I suggest that the Church should act more intensely, integrated with science, in the political intermediation that searches for solutions for our environmental problems. Religious morality could help to restore the economical benefits resulting from the sustainable use of genetic biodiversity to local cultures. I also foresee a larger role of the church in promoting human perceptions regarding the benefits involved in obtaining a more sustainable relationship with nature and in promoting a more rational exploitation of natural resources. The conservation of biodiversity represents a moral matter demanding urgent legislation for the survival of natural ecosystems and, ultimately, of the human species.